Gap Junctions Between Striatal D1 Neurons and Cholinergic Interneurons - Ren, Yuqi; Liu, Yang; Luo, Minmin (Frontiers in Cellular Neuroscience, 2021)
The striatum participates in numerous important behaviors. Its principal projection neurons use GABA and peptides as neurotransmitters and interact extensively with interneurons, including cholinergic interneurons (ChIs) that are tonically active. Dissecting the interactions between projection neurons and ChIs is important for uncovering the role and mechanisms of the striatal microcircuits. Here, by combining several optogenetic tools with cell type-specific electrophysiological recordings, we uncovered direct electrical coupling between D1-type projection neurons and ChIs, in addition to the chemical transmission between these two major cell types. Optogenetic stimulation or inhibition led to bilateral current exchanges between D1 neurons and ChIs, which can be abolished by gap junction blockers. We further confirmed the presence of gap junctions through paired electrophysiological recordings and dye microinjections. Finally, we found that activating D1 neurons promotes basal activity of ChIs via gap junctions. Collectively, these results reveal the coexistence of the chemical synapse and gap junctions between D1 neurons and ChIs, which contributes to maintaining the tonically active firing patterns of ChIs.